Malaysia tour package website using rule-based expert system - Ng Yee, Shian (2012)
Currently, there have been many tourism websites that offered holiday package booking services. However, not many did offered holiday package recommendation. “Malaysia Tour Package Website Using Rule-Based Expert System” is a web-based application purposely to provide customers with valuable recommendations based on their preferences. Thus, these recommendations are provided by an artificial intelligence (AI) based engine which will use the rule-based system. The tour package rule-based recommender system is a flexible rule-based. This is because the rule-based is depend on user criteria to recommender tour package for user and it is a way to help tourist to make decision when they go for a holiday. Besides that, this “Malaysia Tour Package Website Using Rule-Based Expert System” also allow tourist to book tour packages. The website consists of three users; they are customer, administrator and office staff. A customer will able to use the tour package recommender system to choose their preferred holiday package and book a tour package is also included. Administrator can promote their holiday packages and maintain the website, while office staff can view customer information for payment approvement. The methodology is based on the Software Development Life Cycle (SDLC) used as a guide to develop the software stage by stage. The ASP.NET, C# Language and MYSQL Server also help to construct the prototype “Malaysia Tour Package Website Using Rule-Based Expert System”.